Designing a Paradigmatic Model for the Development of Sports for Persons with Disabilities in Iraq - Awfi Al-Shaibawi , Najah Abdul Hassan; Tabesh , Saeid; Dousti, Morteza; Seifari, Masoumeh Kalateh; Ashouri, Taghi (مجلة دراسات وبحوث التربية الرياضية, 2025)
This research aims to design a paradigmatic model for the development of sports for persons with disabilities in Iraq using grounded theory. This research is qualitative and aimed at being developmental-applicative. Participants included 21 experts and specialists in the field of sports for persons with disabilities in Iraq, who were selected through purposeful sampling using a snowball method for interviews. Data analysis was conducted through open, axial, and selective coding of interviews until theoretical saturation was achieved. Conclusion: The development of sports for persons with disabilities in Iraq requires a comprehensive and holistic approach. It is suggested that a national committee consisting of representatives from the government, NGOs, sports federations, and persons with disabilities be formed to coordinate and supervise the implementation of development programs